Effects of Different Organic Manure Applications on the Essential Oil Components of Turkish Sage (Salvia fruticosa Mill.) - Kocabas, Isin; Kaplan, Mustafa; Kurkcuoglu, Mine; Husnu Can Baser, Kemal (Asian Journal of Chemistry, 2010)
The effects of different organic manure applications on chemical composition of essential oils of sage (Salvia fruticosa Mill.) were investigated. Cattle, sheep and poultry manure were used. The essential oil yields increased with organic manure applications and the highest values were found with poultry manure + sheep manure (2.9 %) applications. Percentage values of 1,8 cineole, the main component of the oil, ranged from 44.0 to 50.7 % with the application of organic manures and the highest values were found in poultry manure + sheep manure (50.7 %). As a result, the essential oil content of Turkish sage increased with organic manure applications and had positive effect on plant growth.